PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN : Survei Persepsional pada Karyawan Divisi Manajemen Sumber Daya Manusia PT. INTI (Persero) Bandung - Melindasari, Mila (2013)
This study is based on the performance of the employees human resources management division in INTI, Inc Bandung. This resulted in a drop in performance that resulted in not achieving the company's corporate goals. Based on the data obtained appear to look degradation of employee job satisfaction. The causes of performance degradation due employees job satisfaction human resources management division in INTI, Inc Bandung to the integration of style leadership are not good. Therefore, the company seeks to improve the integration of style leadership that occur so as not to impact negatively on the company but a positive impact on employee job satisfaction improvement. The purpose of this study conducted for:1) To know the description of style leadership in employees human resources management division in INTI, Inc Bandung, 2) To know the description of the employees job satisfaction human resources management division in INTI, Inc Bandung, 3) To determine how much the effect of style leadership of employee job satisfaction human resources management division in INTI, Inc Bandung. Objects in this study were employees human resources management division in INTI, Inc Bandung. The Indepent Variable in this study is style leadership of employee job satisfaction as a dependent variable. Kind of research that is in use is descriptive verificative and the method is in use explanatory survey method with saturated sample technique with a sample 37 respondents. The analysis technique is in use is simple linear regression analysis with the tool SPSS 16.0 software. In this study stated that 1) Style leadership in employees human resources management division in INTI, Inc Bandung were on medium category, 2) Employees job satisfaction human resources management division in INTI, Inc Bandung were on medium category, 3) Style leadership gives positive effect on the employees job satisfaction with high corellation and amount of style leadership influence on the employees job satisfaction is equal to 65,7% and the remainder by 34,3% influenced by other factor. Based on the results of this study is recommende as the basics for other research about style leadership with different indicators and object. Keywords : Style Leadership, Employees Job Satisfaction